2020
DOI: 10.1007/s11069-020-04079-5
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a storm surge forecasting/hindcasting modelling system for the extensive Río de la Plata Estuary and its adjacent Continental Shelf

Abstract: The Río de la Plata (RdP) Estuary is affected by significant surges several times per year. This phenomenon has historically caused catastrophic water-level enlargements of up to 4.44 m, threatening and claiming human lives and producing major economic and material damages. The negative surges are less frequent, but when they do occur, inhibit the access to the principal harbors and waterways and disable the drinking water intakes of the Metropolitan Area of Buenos Aires (the Capital City of Argentina) with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…To capture a large number of surge events, the quality of the EHS was assessed for the long time period between 2000 and 2010. This period was chosen because (a) it is a recent period which is properly represented by ERA5 (Dinápoli et al ., 2014b), (b) during this period the ten most extreme storm surge of the last two decades took place, (c) the numerical model was validated for this period and showed a good ability to reproduce these ten extreme events (Dinápoli et al ., 2020c), and (d) wind speed (OB) and water level (Palermo station) time series are available, which are long enough to obtain statistically robust results. Firstly, wind speed from ERA5 was compared to observations in order to determine whether the reanalysis represents the forcing uncertainties.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…To capture a large number of surge events, the quality of the EHS was assessed for the long time period between 2000 and 2010. This period was chosen because (a) it is a recent period which is properly represented by ERA5 (Dinápoli et al ., 2014b), (b) during this period the ten most extreme storm surge of the last two decades took place, (c) the numerical model was validated for this period and showed a good ability to reproduce these ten extreme events (Dinápoli et al ., 2020c), and (d) wind speed (OB) and water level (Palermo station) time series are available, which are long enough to obtain statistically robust results. Firstly, wind speed from ERA5 was compared to observations in order to determine whether the reanalysis represents the forcing uncertainties.…”
Section: Resultsmentioning
confidence: 98%
“…It should be noted that Dinápoli et al . (2020c) have shown that surface wind is spatially homogeneous (in both timing and amplitude) over the RdP; thus, OB is representative of the region. In addition, the time‐scale of the surge is from hours to days and, therefore, 1 year of hourly data is enough to obtain statistically significant conclusions.…”
Section: Methodology and Datamentioning
confidence: 99%
See 3 more Smart Citations